Bridging the Audit Expectation Gap: A Systematic Review of Stakeholder Perspectives and Reform Initiatives - Andi Nurrahma Gaffar; Adriansyah, Adriansyah; Yulia Yunita Yusuf; Suhartono (Program Studi Perbankan Syariah, IAIN Palopo, 2025)
This study systematically reviews the phenomenon of the Audit Expectation Gap (AEG), which reflects the disparity between what the public expects from auditors and what auditors are professionally required to deliver. Using a Systematic Literature Review (SLR) based on PRISMA 2020, thirty-five peer-reviewed articles published between 2010 and 2025 were analyzed across various countries and stakeholder perspectives. The findings reveal that AEG is a multidimensional issue shaped by technical, social, and communicative factors. Five dominant determinants were identified: auditor competence, professional independence, regulatory complexity, communication transparency, and public literacy. Although reforms such as Key Audit Matters (ISA 701), EU Directive 2014/56/EU, and the establishment of Public Oversight Boards have enhanced institutional credibility, they have not fully closed the trust gap between auditors and society. The study highlights the critical role of audit education and stakeholder literacy in reducing cognitive and social gaps, while recommending a shift toward a communication-based expectation model integrating digital audit ethics and trust-building mechanisms.